Talking about abortion in order to restore women’s freedom. Restarting from self-determination as responsibility of the pregnant woman (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In many countries there are clear signs of the persistence of patriarchy. The article argues that the attempts to question abortion rights in those legal orders derive from such forces and share illiberal tendencies. Based on such premise, it is necessary to rethink access to abortion in light of a woman’s full self-determination regarding procreative choices, which is tied to a sense of responsibility to herself and to the fetus.
Keywords: Patriarchy; abortion; procreative freedom; self-determination; responsibility principle